2014
DOI: 10.1371/journal.pone.0098216
|View full text |Cite
|
Sign up to set email alerts
|

A Treatment with a Protease Inhibitor Recombinant from the Cattle Tick (Rhipicephalus Boophilus microplus) Ameliorates Emphysema in Mice

Abstract: AimsTo determine whether a serine protease inhibitor treatment can prevent or minimize emphysema in mice.MethodsC57BL/6 mice were subjected to porcine pancreatic elastase (PPE) nasal instillation to induce emphysema and were treated with a serine protease inhibitor (rBmTI-A) before (Protocol 1) and after (Protocol 2) emphysema development. In both protocols, we evaluated lung function to evaluate the airway resistance (Raw), tissue damping (Gtis) and tissue elastance (Htis). The inflammatory profile was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 31 publications
3
33
0
3
Order By: Relevance
“…After 21 days of PPE instillation we observed an increase in the proportion of elastin in mice lungs, which is in agreement with previous studies [ 22 , 25 ]. However, many studies indicated that despite the increased elastin content after emphysema development, these fibers are non-functional due to their molecular complexity, which renders repair processes of these fibers inefficient leading to impairment of lung function [ 16 , 47 ], as showed previous by our group after 21 days of the emphysema induction using this same experimental model [ 30 ].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…After 21 days of PPE instillation we observed an increase in the proportion of elastin in mice lungs, which is in agreement with previous studies [ 22 , 25 ]. However, many studies indicated that despite the increased elastin content after emphysema development, these fibers are non-functional due to their molecular complexity, which renders repair processes of these fibers inefficient leading to impairment of lung function [ 16 , 47 ], as showed previous by our group after 21 days of the emphysema induction using this same experimental model [ 30 ].…”
Section: Discussionmentioning
confidence: 66%
“…Then, both lungs were fixed using 10% buffered formalin infused through the trachea at a constant pressure of 20 cm H 2 0 for 24 hours, embedded in paraffin and cut into 5 μm coronal sections. Lung tissue sections were stained with H&E for lung structure analysis [ 30 ]. For PCR analysis, lungs were carefully dissected from the mediastinum and immediately immersed in RNAlater stabilizer and RNA storage solution (Applied Biosystems Canada, Streetsville, ON, Canada) at room temperature, preserved overnight at 4°C and subsequently stored at -80°C until further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…BmTI-A does not change prothrombin and thrombin time, but increases the activated partial thromboplastin time (aPTT), and it has recently been suggested to inhibit angiogenesis in an in vitro vessel formation assay (Soares et al, 2016). In addition, the use of rBmTI-A as a therapy in elastase-induced experimental emphysema appears to minimize parenchymal lesions in mice, suggesting the potential application of this inhibitor in emphysema treatment (Lourenço et al, 2014). Other R. microplus Kunitz-type inhibitors include BmTI-6, a three-Kunitz-domain plasmin inhibitor expressed in the ovary and fat body ; Rhipicephalus microplus kallikrein (RmKK) inhibitor a two-Kunitz-domain inhibitor active against trypsin and tissue/pancreatic kallikrein (Abreu et al, 2014); and boophilin, an anticoagulant and antithrombotic two-Kunitz-domain inhibitor expressed in the midgut of fully engorged females, which inhibits thrombin, elastase, kallikrein, cathepsin G and plasmin (Macedo-Ribeiro et al, 2008.…”
Section: Roles Of Peptidase Inhibitors In the Tick−host Interfacementioning
confidence: 99%
“…Entretanto, como já descrito por Lourenço e col. (56) , ambos os modelos demonstraram aumento do processo inflamatório com aumento da densidade de células positivas para MAC-2, MMP-12 e MMP-9.…”
Section: Marcadores De Fenótipo M2 No Lavado Broncoalveolarunclassified